ANALISIS PENERAPAN PP NO. 71 TAHUN 2010 TENTANG STANDAR AKUNTANSI PEMERINTAHAN PADA KANTOR WILAYAH KEMENTERIAN AGAMA PROVINSI SULAWESI UTARA - Nindy Chelsy Paputungan; Hendrik Manossoh; Sintje Rondonuwu (GOING CONCERN : JURNAL RISET AKUNTANSI, 2023)
Implementation of Government Regulation Number 71 of 2010 related to the Budget Realization Report is an important factor in government financial reporting. The purpose of this study is to analyze the application of Government Regulation Number 71 of 2010 concerning government accounting standards related to PSAP Number 02 Budget Realization Reports at the Regional Office of the Ministry of Religion of North Sulawesi Province. The method used is qualitative research with a descriptive approach. The results of the study show that the implementation of Government Regulation Number 71 of 2010 Government Accounting Standards related to PSAP Number 02 Budget Realization Report at the Regional Office of the Ministry of Religion of North Sulawesi Province, based on four elements consisting of the Budget Realization Report structure, reporting period, timeliness and the contents of the Budget Realization Report, overall the implementation is quite good and appropriate but not yet fully maximized because in the content elements of the Budget Realization Report, discrepancies were found where there were three items that were not presented in the Budget Realization Report, namely transfer items because the Regional Office of the Ministry of Religion of North Sulawesi Province did not make transfers in cash, surplus/deficit items were not presented in the Report Realization of the Budget but presented in operational reports and remaining items of over/under budget financing (SILPA/SIKPA) are not presented because if there is over/under budget financing (SILPA/SIKPA) it will be returned directly to the state treasury.Keywords : Government Accounting Standards, Financial Reporting, Budget Realization Reports, Budget Financing